MBCL-24. INCIDENCE AND RISK FACTORS OF POSTERIOR FOSSA SYNDROME IN CHILDREN WITH POSTERIOR FOSSA TUMORS. Issue 2 (22nd June 2018) - Sato, Mariko; Eble, Demi; Sasaki, Tomoaki; Zimmerman, Bridget; Menezes, Arnold; Greenlee, Jeremy; Wilson, Saul; Dlouhy, Brian; Matsumoto, Satsuki; Boes, Aaron; O'Dorisio, Sue
Abstract: BACKGROUND: The pathophysiology of posterior fossa syndrome (PFS) are not completely unraveled and its unpredictable outcome makes the clinical management of PFS challenging. OBJECTIVE: To examine the incidence, clinical outcome and prognostic risk factors for PFS. METHODS: The retrospective chart review from 1976 to March 2017 was conducted and medical records of 87 children with posterior fossa tumors were analyzed to look for outcomes, clinical variables such as tumor type, presentation and surgical methods. Pre- and post-operative MRI features of 64 patients were evaluated whether a damage was present or not in an anatomical structure for PFS prediction using a chi-square test. RESULTS: Of the 87 charts reviewed 48 (55%) had medulloblastoma, 26 (30%) had low grade glioma, 10 (11%) had ependymoma, and 3 (3%) had ATRT. Fifteen (17%) patients developed PFS, 10 (67%) had medulloblastoma, 2 (13%) had low grade glioma, 2 (13%) had ATRT, and 1 (7%) had ependymoma. Ten out of 15 patients (67%) with PFS had severe PFS symptoms. Among observed clinical variables, the intraoperative incision in the vermis was highly associated with the incidence of PFS (p=0.009). In the post-operative MRI, the damage of bilateral dentate nuclei and superior cerebellar peduncles were detected significantly in PFS (P=0.008 and p=0.018, respectively). CONCLUSION: Symptoms of PFS vary thus retrospective chart review may underestimate the actual incidence. Post-operative MRI findings may be predictive of PFS and may lead to prevention or to early interventions.